2010
DOI: 10.1016/j.ibmb.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone and allatostatins in the German cockroach embryo

Abstract: Levels of juvenile hormone III (JH), FGLamide allatostatin peptides (ASTs), ASTs precursor (preproAST) mRNA and methyl farnesoate epoxidase (CYP15A1) mRNA were measured in embryos of the cockroach Blattella germanica. JH starts to rise just after dorsal closure, reaches maximal levels between 60% and 80% of embryogenesis, and decrease subsequently to undetectable levels. ASTs show low levels during the first two thirds of embryogenesis, increase thereafter and maintain high levels until hatching. PreproAST mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…In a similar manner as CYP15C1 expression in B. mori , CA-specific CYP15 expression has also been observed in two cockroach species, D. punctata and Blattella germanica [18], [34], in the locust Schistocerca gregaria [35], and in the mosquito Aedes aegypti [36], suggesting a conserved function in JH biosynthesis. However, the enzymatic properties of CYP15 products, with the exception of those of D. punctata [18] and B. mori (this study), have not been studied and the physiological role of CYP15 s in the development of other insects remains unknown.…”
Section: Discussionmentioning
confidence: 54%
“…In a similar manner as CYP15C1 expression in B. mori , CA-specific CYP15 expression has also been observed in two cockroach species, D. punctata and Blattella germanica [18], [34], in the locust Schistocerca gregaria [35], and in the mosquito Aedes aegypti [36], suggesting a conserved function in JH biosynthesis. However, the enzymatic properties of CYP15 products, with the exception of those of D. punctata [18] and B. mori (this study), have not been studied and the physiological role of CYP15 s in the development of other insects remains unknown.…”
Section: Discussionmentioning
confidence: 54%
“…This apparent Cyp15A1 pseudogene, which has only 0.027‐fold expression levels relative to Cyp15F1 , was not considered further in the current work. However, it is noteworthy that a truncated Cyp15A1 homolog was also identified in the cockroach B. germanica (Maestro et al, ); and also several Cyp4 pseudogenes were previously identified in R. flavipes (Zhou et al, ). Further, a null mutant with a 68‐bp deletion was identified in B. mori Cyp15C1 that eliminates JH production (Daimon et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of genomic contamination was confirmed using a control without reverse transcription. Gene expression was analyzed by quantitative real-time PCR using iQ SYBR Green supermix in an iQ cycler and iQ single color detection system and the iQ5 optical system software v. 2.0 (Bio-Rad Laboratories, Hercules, CA, USA), as previously described (Maestro et al, 2010). Primers used to amplify total BgJHAMT as well as the different 3 -UTR isoforms can be found in Table S1.…”
Section: Rna Extraction Cdna Synthesis and Real-time Pcr Analysesmentioning
confidence: 99%
“…In cockroaches, and in most other groups, it is proposed that methylation of farnesoic acid (FA) to produce methyl farnesoate (MF) precedes epoxydation to JH (Hammock, 1975), whereas in Lepidoptera, the proposed way is epoxydation of FA and then methylation of juvenile hormone acid (JHA) (Goodman & Cusson, 2012). The enzyme that catalyzes the epoxidation is a cytochrome P450, CYP15A1, or JH epoxydase, that has already been characterized in B. germanica (Maestro et al, 2010). Independently of the order of the reactions, the enzyme that catalyzes the methylation is usually called JH acid O-methyltransferase (JHAMT).…”
Section: Introductionmentioning
confidence: 99%